(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Marangoni convection problem is studied for hybrid nanofluids. The problem is studied for both positive and negative Marangoni parameters. The magnetohydrodynamic (MHD) flow of heat transfer over a stretching disk with porous suction and injection effects is examined. The problem is converted from partial differential equations (PDEs) into ordinary differential equations (ODEs) by employing similarity transformation method. Then, it is solved numerically by using the bvp4c solver in MATLAB. The effects of skin friction and Nusselt number for various selected values representing water concentration and Marangoni effects, along with nano particles comprises water, ZnO2 and MWCNT by incorporating the influence of suction and injection. Furthermore, we present detailed results in terms of radial velocity profile, axial velocity profile, and temperature profile under suction and injection effects, even for negative Marangoni parameters by comparing water, ZnO2, MWCNT nano particles. Additionally, we provide a comparative analysis with existing literature, presenting the skin friction and Nusselt number results in a table format. This holistic approach offers a comprehensive understanding of the intricate heat transfer dynamics in MHD nanofluids over stretching disks with porous media effects, contributing to advancements in thermal fluid dynamics and providing valuable insights for engineering applications in diverse fields.